2022
DOI: 10.3389/fmolb.2022.843391
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Key Foreign Body Reaction-Related Transcription Factors and Genes Through Transcriptome Analysis

Abstract: Background: Silicone implants are widely used in the field of plastic surgery for wound repair and cosmetic augmentation. However, molecular mechanisms and signaling pathways underlying the foreign body reaction (FBR) of a host tissue to the silicone require further elucidation. The purpose of this study was to identify key FBR-related transcription factors (TFs) and genes through transcriptome analysis.Methods: We used a rat model with a subcutaneous silicone implant in the scalp and performed high throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…These general trends were reproduced in the present study for RAW-Blue macrophages cultured on the 10% FBS-conditioned surfaces. Furthermore, the absence of an effect due to TLR2 inhibition supports established views that macrophage activation in traditional culture environments that use serum-derived adsorbed protein layers does not involve TLR2 and may explain why this signaling pathway has been largely overlooked in sterile biomaterial-induced inflammation and FBR until recently (Li et al, 2019;Liu et al, 2022). Frontiers in Bioengineering and Biotechnology frontiersin.org…”
Section: The Effect Of Lysate-conditioned Teflon™ Af Surfaces On Macr...supporting
confidence: 64%
See 1 more Smart Citation
“…These general trends were reproduced in the present study for RAW-Blue macrophages cultured on the 10% FBS-conditioned surfaces. Furthermore, the absence of an effect due to TLR2 inhibition supports established views that macrophage activation in traditional culture environments that use serum-derived adsorbed protein layers does not involve TLR2 and may explain why this signaling pathway has been largely overlooked in sterile biomaterial-induced inflammation and FBR until recently (Li et al, 2019;Liu et al, 2022). Frontiers in Bioengineering and Biotechnology frontiersin.org…”
Section: The Effect Of Lysate-conditioned Teflon™ Af Surfaces On Macr...supporting
confidence: 64%
“…MyD88-deficient mice had reduced inflammatory cell recruitment and thinner fibrous capsules when compared to wild type mice, 28 days after PEG hydrogel implantation (Amer et al, 2019). In a recent study by Liu and colleagues identified the TLR2-encoding gene Tlr2 as a critical gene hub in the FBR to silicone implants in rats (Liu et al, 2022).…”
Section: Emerging Evidence That Tlr2 Mediates Biomaterials Host Respo...mentioning
confidence: 99%
“…4G). 58 Informed by KEGG analysis outcomes, more detailed evaluations of gene subsets were conducted, beginning with those related to innate immune cell (e.g., neutrophil and macrophage) phenotype and activation. As shown in Fig.…”
Section: Transcriptomics Reveals Molecular-level Signaling Profile Co...mentioning
confidence: 99%
“…Several transcription factors (Fos, FosL1, LEF1, TCF7, HMGA1, ELF5, IRF4, SPI1) have also been identified that may be crucial in skin soft tissue expansion [ 48 , 107 ]. FOS and FOSL1 are members of the Fos gene family and the proteins encoded by them can dimerize with Jun family proteins to form the transcription factor complex AP-1.…”
Section: Molecular Mechanismmentioning
confidence: 99%
“…We discussed previously that mechanical stretch can induce the activation of Wnt/β-catenin signaling pathway to promote skin soft tissue expansion. ELF5, IRF4, and SPI1 are important transcription factors that regulate the differentiation, activation, and proliferation of immune cells and are believed to be involved in the foreign body response to silicone during tissue expansion [ 107 ].…”
Section: Molecular Mechanismmentioning
confidence: 99%